2003
DOI: 10.1177/000331970305400218
|View full text |Cite
|
Sign up to set email alerts
|

Left Cervical Aortic Arch Associated with Aortic Aneurysm, Aortic Coarctation, and Branch Artery Aneurysm

Abstract: Cervical aortic arch (CAA) is a rare congenital aortic anomaly. Although, in CAA, other cardiovascular abnormalities including aortic aneurysm and aortic coarctation are occasionally accompanied, coexistence of those 2 aortic abnormalities on the same patient is rare, and moreover, association of the aneurysm of branching artery has not been reported. The authors present here the first patient with CAA who had both an aneurysm and a coarctation in the aortic arch, and further, another aneurysm in the left subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Noguchi et al repaired another Haughton D type LCAA aneurysm in a 59 year old man with a dacron interposition graft from just beyond LCCA to the beginning of distal transverse aorta (DTA) with branch reconstruction of LSA, under total circulatory arrest (TCA) [9]. Tsukamoto et al described repair of LCAA aneurysm with LSA aneurysm and coarctation [10] and Imai et al reported reconstruction with interposition graft of LCAA with coarctation [11]. Hirao et al reported LCAA aneurysm which had been thought to be a mediastinal tumour [12], and Higuchi employed left thoracotomy and partial cardiopulmonary bypass through descending aorta and IVC to repair LCAA aneurysm just distal to LCCA with aberrant and tortuous LSA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Noguchi et al repaired another Haughton D type LCAA aneurysm in a 59 year old man with a dacron interposition graft from just beyond LCCA to the beginning of distal transverse aorta (DTA) with branch reconstruction of LSA, under total circulatory arrest (TCA) [9]. Tsukamoto et al described repair of LCAA aneurysm with LSA aneurysm and coarctation [10] and Imai et al reported reconstruction with interposition graft of LCAA with coarctation [11]. Hirao et al reported LCAA aneurysm which had been thought to be a mediastinal tumour [12], and Higuchi employed left thoracotomy and partial cardiopulmonary bypass through descending aorta and IVC to repair LCAA aneurysm just distal to LCCA with aberrant and tortuous LSA [13].…”
Section: Discussionmentioning
confidence: 99%
“…CAA is defined by aortic arch situated cranially above the clavicle [2]. Major clinical findings include palpable neck mass, dysphagia, wheezing, coughing, stridor, choking, apneic spells, and recurrent pulmonary infection, even traumatic aortic rupture, or no symptoms at all, depending on the location and extent with or without aneurysm formation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…A rarer finding is CAA with aneurysm formation, which constitutes about 20% of all cases [2]. The cause of this congenital anomaly is the persistence of second or third dorsal arch, confluence of third and fourth dorsal arches, or failure of normal caudal migration of the fully developed fourth arch [2,3]. Other congenital anomalies such as tetralogy of Fallot, ventricular septal defect or double-outlet right ventricle are associated in 30% of CAAs [4].…”
Section: Introductionmentioning
confidence: 99%
“…The arch had been bypassed without CPB through a median sternotomy. Also, extra-anatomic bypass of the right aortic arch [4][5][6] for coarctation has recently been reported. The right-sided aortic arch is mostly asymptomatic and found incidentally in the adult, unless aneurysms develop.…”
Section: Discussionmentioning
confidence: 99%